Deforestation Trends in the Congo Basin : Logging - Doetinchem, Nina (World Bank, Washington, DC, 2014)
The Congo Basin has the largest forest cover on the African continent. Of the 400 million hectares that the Basin comprises, about 200 million of them are covered by forest, with 90 percent being tropical dense forests. The Congo Basin's logging sector has a dualistic configuration. It boasts a highly visible formal sector that is export oriented and dominated by large industrial groups with foreign capital and an informal sector that has long been underestimated and overlooked. This report is one of a series of reports prepared during a two-year attempt to analyze and better understand deforestation dynamics in the Basin. It presents findings related to the logging sector and its potential impact on forest cover, and it is based on an in-depth analysis of the sector. The paper's structure is as follows: first chapter gives an overview of the logging sector both formal and informal in the six countries and its importance in terms of employment and revenues; second chapter is the analyzes and impacts of logging activities on forest cover; and final chapter presents recommendations to foster sustainable logging activities with a particular focus on the informal sector and reduce potential adverse impact on natural forests.